Pengembangan Rubrik Penilaian Menulis Teks Laporan Observasi di Madrasah: Implementasi Taksonomi Bloom dalam Pembelajaran - Sukenti, Desi; Anggraini , Regina (Jurnal Pendidikan Agama Islam Al-Thariqah, 2025)
This study uses Bloom's Taxonomy in developing a rubric for assessing observational report text writing skills in Madrasah. The research method is descriptive qualitative, and data were collected through observation, interviews, and analysis of students' writing results. Five Indonesian language teachers and 25 students participated in this study. The findings revealed that the application of Bloom's Taxonomy in the assessment rubric focuses on cognitive assessment at the two lowest levels, namely knowledge (C1) and understanding (C2). This study also identified five benefits of implementing Bloom's Taxonomy, especially in motivating students and improving learning performance based on clear and measurable criteria. Therefore, this assessment helps teachers and students achieve teaching and student learning objectives more effectively. The findings presented have important implications for the development of Indonesian language learning curriculum in madrasah, improving students' basic literacy competencies, creating competency achievement indicators for lesson implementation plans, and achieving educational goals at the local and national levels.